بانگەوازی ئاینی لەفەیسبوك و كاریگەرێتی لەسەر خوێندكارانی زانكۆی سلێمانی - مؤمن, م.عادل حمە عارف (Sulaimani Journal for Humanities, 2023)
The title of the study is: (Religious preaching on Facebook and its impact on the students of Sulaimani University), which discusses two variables: (religious preaching on Facebook) and (Students of Sulaimani University), which determines the impact of first variable on the second variable, the survey form was distributed to the sample of the study, with the aim of answering the question: What is the extent of the impact of religious preaching on Facebook on the students of the University of Sulaimani? The study pursues this goal and attempts to achieve it. This study is divided into three main parts: The first part is the methodology: which discusses (Research problem, Importance of the research, Research Objectives, The scope of research, The type of research method, Validity and Reliability of the research, Determining the concepts). The second part is the framework of the research theory and consists of three concepts: the first concept is about (introducing the concept of preaching and history of preaching, meanings of preaching in the Qur'an, dimensions of preaching, ways of preaching, characteristics of preachers). The second concept describes (the concept of Facebook، The historical development of Facebook and its functions, the positive and negative aspects of Facebook، errors and problems in the field of call). Historical development and functions of Facebook, positive and negative aspects of Facebook, mistakes and problems in the field of preaching). The third part includes the practical aspects of the research (research community and research sample, Preparation and distribution of survey form, determining the Validity of the survey form, Presentations and discussions of the results). Finally, the study has come up with a number of conclusions، suggestions and recommendations.
Keywords: Religious Preaching; Influence; Facebook; Students